Barbados. Significant achievements 2015 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The main activities carried out by the Institute in Barbados during 2015 are identified, with respect to the needs and interests of the country, strengthening issues such as agrotourism, innovation, technology, greenhouses, nutrition, beekeeping, horticulture, composting, resilience against climate change and organic agriculture. Likewise, work was done on artificial insemination, water storage, international trade and the inclusion of women and youth in agriculture. Finally, the strengthening of the value chains of hot peppers, blackbelly sheep, rabbits and crops was supported.